Unified theory of Alzheimer's disease (UTAD): implications for prevention and curative therapy. Issue 1 (December 2016) - Nehls, Michael
Abstract The aim of this review is to propose a Unified Theory of Alzheimer's disease (UTAD) that integrates all key behavioural, genetic and environmental risk factors in a causal chain of etiological and pathogenetic events. It is based on three concepts that emanate from human's evolutionary history: (1) The grandmother-hypothesis (GMH), which explains human longevity due to an evolutionary advantage in reproduction by trans-generational transfer of acquired knowledge. Consequently it is argued that mental health at old-age must be the default pathway of humans' genetic program and not development of AD. (2) Therefore, mechanism like neuronal rejuvenation (NRJ) and adult hippocampal neurogenesis (AHN) that still function efficiently even at old age provide the required lifelong ability to memorize personal experiences important for survival. Cumulative evidence from a multitude of experimental and epidemiological studies indicate that behavioural and environmental risk factors, which impair productive AHN, result in reduced episodic memory performance and in reduced psychological resilience. This leads to avoidance of novelty, dysregulation of the hypothalamic–pituitary–adrenal (HPA)-axis and cortisol hypersecretion, which drives key pathogenic mechanisms of AD like the accumulation and oligomerization of synaptotoxic amyloid beta, chronic neuroinflammation and neuronal insulin resistance. (3) By applying to AHN the law of the minimum (LOM), which defines the basic requirements of biological growth processes, the UTAD explains why and how different lifestyle deficiencies initiate the AD process by impairing AHN and causing dysregulation of the HPA-axis, and how environmental and genetic risk factors such as toxins or ApoE4, respectively, turn into disease accelerators under these unnatural conditions. Consequently, the UTAD provides a rational strategy for the prevention of mental decline and a system-biological approach for the causal treatment of AD, which might even be curative if the systemic intervention is initiated early enough in the disease process. Hence an individualized system-biological treatment of patients with early AD is proposed as a test for the validity of UTAD and outlined in this review.